RESTORATION OF TRUTH THROUGH CHRISTIAN EDUCATION IN THE MIDST OF A CULTURE OF LOST TRUTH: A REVIEW OF EPISTEMIC RELATIVISM AND HOAXES - Sabarani Waruwu; Andar Gunawan Pasaribu (ASIAN PUBLISHER, 2025)
The crisis of truth in the digital era has given rise to a phenomenon called lost truth, which is a situation in which the boundaries between facts and opinions are blurred due to the dominance of epistemic relativism and the spread of hoaxes. This phenomenon has a serious impact on the moral, spiritual, and social order of society, including in the Christian community. This article aims to analyze how Christian education can play a role as a means of restorative truth in a post-truth culture by reviewing the roots of the philosophy of knowledge, theological perspectives, and relevant pedagogical strategies. This research uses a contextual theological and transformative educational approach, by integrating literature review and interviews from educators, theologians, and church leaders. The results of the study show that epistemic relativism weakens society's orientation towards objective truth and encourages the birth of a culture of information consumption without verification. The church and Christian educational institutions have a central role to restore this orientation through learning that emphasizes moral character building, the strengthening of critical reasoning, and faith-based digital literacy. The proposed model of truth restoration combines three main dimensions: (1) the establishment of the integrity and ethics of biblical truth; (2) strengthening the ability to think critically and discern digital information; and (3) the integration of faith, knowledge, and the practice of daily life. Thus, Christian education is not just a tool for knowledge transfer, but also a spiritual instrument for building a resilient, critical, and God-rooted society in the midst of the global disinformation tide.